Estudo geocronológico de sedimentos correlatos à Formação Rio Claro - Salmazo, Giovana Oliveira [UNESP] (2015)
The sedimentary deposition range of Rio Claro Formation until now remained among controversies because it was not done a precise and direct geochronological study. With the use of quartz as a common dosimeter of sedimentary formation, it was possible to evaluate using thermoluminescence that sedimentation occurred in Upper Pleistocene. To ensure the accuracy of the results obtained, It sought to improve the dosimetric technique used by the laboratory. The characterization of luminescent properties of the sedimentary quartz grains showed that OSL signal of all samples was saturated and some sample showed TL signal saturated too. Saturation is due to the sediments have fluvial origin. TL signal of the samples DS 01 and DS 06 it was saturated. The TL age was obtained for both. A study related to technical limitation TL showed that the quartz has two stages of saturation. The TL dating uses only the first stage of saturation because laboratory irradiation satisfactorily reproduces the same TL signal behavior generated in nature